The impact of the built environment on health across the life course: Design of a cross-sectional data linkage study - Villanueva, K.; Pereira, Gavin; Knuiman, M.; Bull, F.; Wood, L.; Christian, H.; Foster, S.; Boruff, B.; Beesley, B.; Hickey, S.; Joyce, S.; Nathan, A.; et al. (BM J Group, 2013)
Introduction: The built environment is increasingly recognised as being associated with health outcomes. Relationships between the built environment and health differ among age groups, especially between children and adults, but also between younger, mid-age and older adults. Yet few address differences across life stage groups within a single population study. Moreover, existing research mostly focuses on physical activity behaviours, with few studying objective clinical and mental health outcomes. The Life Course Built Environment and Health (LCBEH) project explores the impact of the built environment on self-reported and objectively measured health outcomes in a random sample of people across the life course. Methods and analysis: This cross-sectional data linkage study involves 15 954 children (0-15 years), young adults (16-24 years), adults (25-64 years) and older adults (65+years) from the Perth metropolitan region who completed the Health and Wellbeing Surveillance System survey administered by the Department of Health of Western Australia from 2003 to 2009. Survey data were linked to Western Australia's (WA) Hospital Morbidity Database System (hospital admission) and Mental Health Information System (mental health system outpatient) data. Participants' residential address was geocoded and features of their 'neighbourhood' were measured using Geographic Information Systems software. Associations between the built environment and self-reported and clinical health outcomes will be explored across varying geographic scales and life stages. Ethics and dissemination: The University of Western Australia's Human Research Ethics Committee and the Department of Health of Western Australia approved the study protocol (#2010/1). Findings will be published in peer-reviewed journals and presented at local, national and international conferences, thus contributing to the evidence base informing the design of healthy neighbourhoods for all residents.